TELEMEDICINE IN THE COVID-19 PANDEMIC - Pelicic, Damir; Dobrovic, Dragica (HEALTH CARE, 2020)
Telemedicine can be broadly defined as the use of telecommunication technologies to provide medical information and services. The COVID‐19 pandemic has once again focused on the use of digital technologies in the daily work of health workers, and above all doctors. Digital technologies enable the doctor to contact the patient via a secure network without personal contact. COVID‐19 has forced us to adapt to the new situation. In Montenegro, the eHealth platform started operating in 2019, and it was upgraded in 2020. The eHealth portal provides information and enables the use of electronic services in the health system of Montenegro. The COVID‐19 electronic service was developed during the COVID‐19 pandemic, and it was intended for the insured people tested for the presence of a new coronavirus, in order to obtain the feedback on test results. In this way, through the electronic model of patient notification, selected doctors are warned on time about the presence of the SARS‐CoV‐2 virus through the information system, before admitting the patient to the clinic, which allows additional precautions, that is, the better prevention and greater protection of doctors and medical staff. The aim of this paper is to show the importance of telemedicine during the COVID‐19 pandemic.